Pemberdayaan Pemasaran UMKM Berbasis Digital di Kelurahan Tlogopatut, Kecamatan Gresik, Kabupaten Gresik - Mujib, Wahyu Abdul; Ikaningtyas, Maharani (Jurnal Bisnis Indonesia, 2024)
Digital marketing has become a crucial element in enhancing the competitiveness of Micro, Small,and Medium Enterprises (UMKM) in various regions. This research aims to examine the efforts toempower digital marketing for UMKM in Tlogopatut Village, Gresik. The research methodologyinvolves surveys, interviews, and data analysis related to the implementation of digital marketingstrategies by MSMEs in this area. The results of the research indicate that empowering digitalmarketing for UMKM holds significant potential for increasing market access and product sales.However, various challenges are faced by UMKM operators in adopting digital marketing strategies,such as a lack of digital technology knowledge and limited digital infrastructure. Therefore,empowerment efforts through training, technical support, and digital infrastructure development areessential to assist UMKM in optimizing their marketing potential. This research provides valuableinsights into the challenges and opportunities of implementing digital marketing in UMKM inTlogopatut Village, Gresik, and offers a foundation for policymakers and local stakeholders to designmore effective empowerment programs.Keywords: Digital Marketing; UMKM; Digital Strategy